2007
DOI: 10.1021/ie070481w
|View full text |Cite
|
Sign up to set email alerts
|

Gas−Liquid Dispersion with Buoyant Particles in a Hot-Sparged Stirred Tank

Abstract: Many industries use gas-liquid stirred-tank reactors with a third phase of buoyant particles. Few studies have looked at the effects of buoyant particle characteristics on solid-liquid suspension and gas-liquid dispersion, and even less have considered operation at elevated temperatures. This paper reports power consumption and gas holdup measurements made in a hot-sparged three-phase system. The vessel was a dished-base reactor of diameter 0.476 m (T) holding 0.145 m 3 of liquid, agitated by a multi-impeller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The detailed calculation of the total power input has been reported in our previous paper. 14 With the same power input and total gas flow rate, including the contribution of the evaporation from the liquid phase, the gas holdup decreases with increasing temperature. Without solids, the gas holdup in cold conditions is over twice that at the highest temperature.…”
Section: Gas Holdup 321 Effect Of the Temperature On The Gas Holdmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed calculation of the total power input has been reported in our previous paper. 14 With the same power input and total gas flow rate, including the contribution of the evaporation from the liquid phase, the gas holdup decreases with increasing temperature. Without solids, the gas holdup in cold conditions is over twice that at the highest temperature.…”
Section: Gas Holdup 321 Effect Of the Temperature On The Gas Holdmentioning
confidence: 99%
“…14,15 The effects of the temperature on the RPD at different solid concentrations are shown in Figure 4a-c. It is clear that when no particles were present, the higher the temperature, the greater the RPD.…”
Section: Gassed Power Demand 311 Effect Of Temperature On the Relmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies of hot gas–liquid systems have shown that the behaviors of dispersed gas under the hot‐sparged conditions differ significantly from those of cold gassed systems . Gas holdup was found to decrease rapidly with increasing temperature according to a power law with an exponent of −3.2 for the absolute temperature from 290 to 368 K, and the overall Sauter mean bubble size in hot systems was about 21% larger than that for cold systems . Both effects can change the gas–liquid interfacial area ( a ) to a great extent.…”
Section: Introductionmentioning
confidence: 96%
“…However, all those reports mainly focused on k L a at ambient temperature when the vapor pressure can be neglected compared with the operating pressure, while many of the processes mentioned above are exothermic and ‘hot’, operating at higher temperatures when the assumption of negligible vapor pressure is likely to be invalid. Moreover, recent studies of hot gas–liquid systems have shown that the behaviors of dispersed gas under the hot‐sparged conditions differ significantly from those of cold gassed systems . Gas holdup was found to decrease rapidly with increasing temperature according to a power law with an exponent of −3.2 for the absolute temperature from 290 to 368 K, and the overall Sauter mean bubble size in hot systems was about 21% larger than that for cold systems .…”
Section: Introductionmentioning
confidence: 99%